Tour(F)ism: An Innovative Start-up Model for Aggregating AquaTourism Experiences - Santhosh Kumar; P.S. Ananthan; Shivaji D. Argade (Journal of Indian Fisheries Association, 2025)
India has made significant strides in fisheries (18.40 million tons; 2nd in aquaculture; 1.12% of national GVA), tourism (5% of GDP; 12.42 lakh direct jobs), start-ups (3rd largest ecosystem; 25% CAGR), eco-tourism (5% of tourism GDP), and agri-tourism (₹60 crore annual revenue in Maharashtra; 0.2% of tourism GDP). Despite this structured growth and progress, aqua-tourism – the intersection of fisheries and tourism—remains underdeveloped and fragmented. Currently, there is no structured model in India to connect fish farmers directly with clients seeking immersive, educational, and leisure-based aqua-tourism experiences. Potential tourists face limited booking options, high transaction costs, and a lack of value-added services. At the same time, many fish farmers are willing to offer but are unequipped due to the lack of expertise, digital access, or marketing channels. Existing centres remain isolated and under-promoted. Tour(F)ism aims to fill this critical gap as India's 1st rural aqua-tourism e-aggregator platform. The initiative moves beyond simple digital aggregation by enhancing the aqua-tourism experience through tourism-focused value additions at fish farms, seamlessly combining education, entertainment, and leisure elements. By reducing transaction costs and eliminating costly intermediaries, the platform empowers fish farmers to diversify their income through tourism. Additionally, it offers clients never-before-authentic, affordable rural aqua-tourism experiences. Thus, by effectively bridging the urban demand with rural supply within the fisheries-tourism interface, this novel platform creates a win-win solution for both fish farmers and clients.